The Effect of Learning Strategies, Academic Ability and the Interaction to the Critical Thinking Skills and Cognitive Learning Outcomes of Natural Science-Biology - Hartono D Mamu (Jurnal Pendidikan Sains, 2014)
Pengaruh Strategi Pembelajaran, Kemampuan Akademik dan Interaksinya terhadap Keterampilan Berpikir Kritis dan Hasil Belajar Kognitif IPA BiologiAbstract: This quasi experimental research is intended to know the teaching strategy, academic abil-ity, and its interaction to the critical thinking skills and cognitive achievement. Pretest-Postest Non Equivalent Control Group Design with factoring style 4 x 2 is carried out. The data are analyzed with Mancova. The result of the research shows: (1) the teaching strategy significantly affect the critical thinking skills and cognitive achievement of the students; (2) the student’s academic ability signifi-cantly influence the critical thinking skills and cognitive achievement of the students; (3) the influence of the interaction of the teaching strategy and the student’s academic ability to the critical thinking skills and cognitive achievement of the students is insignificant.Key Words: teaching strategy, academic ability, critical thinking skills, cognitive achievementAbstrak: Penelitian quasi eksperimen ini bertujuan untuk untuk mengetahui pengaruh strategi pembel-ajaran, kemampuan akademik, dan interaksinya terhadap keterampilan berpikir kritis dan hasil belajar kognitif. Pretest-Postest menggunakan  Non Equivalent Control Group Design dengan pola faktorial 4 x 2. Data dianalisis dengan Mancova. Hasil penelitian menunjukkan: (1) strategi pembelajaran ber-pengaruh secara signifikan terhadap keterampilan berpikir kritis dan hasil belajar kognitif siswa; (2) kemampuan akademik berpengaruh secara signifikan terhadap keterampilan berpikir kritis dan hasil belajar kognitif siswa; (3) interaksi strategi pembelajaran dan kemampuan akademik tidak berpengaruh terhadap keterampilan berpikir kritis dan hasil belajar kognitif siswa.Kata kunci: strategi pembelajaran, kemampuan akademik, keterampilan berpikir kritis, hasil belajar kognitif